Pengaruh Citra Merek dan Harga terhadap Keputusan Pembelian Produk Scarlett di Kota Unaaha - Melati Melati; Aci Alpadilla Septarina (Universitas Batanghari Jambi, 2022)
This study aims to examine and analyze empirically the influence of brand image and price on purchasing decisions for Scarlett products in Unaaha City. This research was conducted in the city of Unaaha. The population in this study were consumers of Scarlett products in the city of Unaaha with a total sample of 50 respondents. The data analysis method is carried out by the Multiple Linear Regression analysis method. Based on the results of the study, it was concluded: That simultaneously or partially there is a positive and significant effect of brand image and price variables on purchasing decisions. This fact shows that the better the brand image and the price given, the greater the level of purchasing decisions for Scarlett Products in Unaaha City.